2017
DOI: 10.1155/2017/3040254
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Dynamics of Gd1−xYxMn2O5 Investigated by Infrared Spectroscopy

Abstract: We present infrared (IR) reflectivity of Gd1-xYxMn2O5 with x = 0, 0.2, 0.4, 0.6, 0.8, and 1 in the frequency range 30–1000 cm−1. A total of 18 IR active phonons were observed for GdMn2O5 (x=0) and three additional phonons have been observed with increasing x, marking a total of 21 phonons in YMn2O5 (x=1). A systematic investigation was performed to map out the structural distortion through the lattice vibration and discuss the consequences of frequency shifts in phonon modes. In addition, we have calculated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
(34 reference statements)
2
3
0
Order By: Relevance
“…Here, we have estimated the indirect energy band gap of about E g ∼ 1.5 eV by extrapolating the linear part of spectrum to the x-axis which is calibrates as energy axis as shown in figure 5. The estimated value of E g is close to the band gap observed for related compounds such as TbMn 2 O 5 ∼ 1.70 eV, YMn 2 O 5 ∼ 1.61 eV, DyMn 2 O 5 ∼ 1.45 eV [12,25].…”
Section: Uv-visible Spectroscopysupporting
confidence: 83%
See 2 more Smart Citations
“…Here, we have estimated the indirect energy band gap of about E g ∼ 1.5 eV by extrapolating the linear part of spectrum to the x-axis which is calibrates as energy axis as shown in figure 5. The estimated value of E g is close to the band gap observed for related compounds such as TbMn 2 O 5 ∼ 1.70 eV, YMn 2 O 5 ∼ 1.61 eV, DyMn 2 O 5 ∼ 1.45 eV [12,25].…”
Section: Uv-visible Spectroscopysupporting
confidence: 83%
“…Remarkably, an electric polarization has been observed at room temperature for GdMn 2 O 5 [11]. We have also reported the vibrational phonon dynamics for GdMn 2 O 5 , DyMn 2 O 5 , and YMn 2 O 5 and find that they exhibits orthorhombic structure and have shown strong structural distortion due to the change in ionic radius of + R 3 [12,13]. A key issue is thus to understand the effect of + R 3 on physical properties, more generally, optical and transport properties of the system at room temperature and above.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…According to lattice dynamics calculations, RMn 2 O 5 compounds exhibit 36 IR active modes at the Γ-point depending on the crystal direction (8B 1u (E||z)+14B 2u (E||y)+14B 3u (E||x)) [18]. However, of those 36 phonon modes, only 13 modes are observed in HMO and are in good agreement with other polycrystalline RMn 2 O 5 (R = Sm, Nd, Gd, Dy, and Y) compounds [19][20][21]. The cause of this difference lies in the polycrystalline nature of our compound having mixed ab-plane and c-axis response.…”
Section: Infrared Reflectivitysupporting
confidence: 62%
“…Structural characterization.-Figure 1a shows the X-ray diffraction patterns of Ho doped GdMn 2 O 5 . The XRD pattern is compared with the literature 18,20 and it is found that the structure is orthorhombic. It is also observed that the peaks shift towards the higher angles as Ho 3+ concentration increases.…”
Section: Resultsmentioning
confidence: 99%